Postoperative keratitis due to Paecilomyces: a rare pediatric case - TOKER, AYŞE EBRU; KEPENEKLİ KADAYİFCİ, EDA; ÇERİKÇİOĞLU, NİLGÜN (AFRICAN FIELD EPIDEMIOLOGY NETWORK-AFENET, 2016)
Fungal infections like Paecilomyces keratitis have emerged in childhood recently. The diagnosis and treatment of Paecilomyces keratitis is difficult and the outcome is usually poor. Corneal culture should be performed on fungal media such as Sabouraud glucose neopeptone agar (SDA) as soon as possible for diagnosis. We report a rare case of Paecilomyces keratitis in an immunocompetent child, which was unresponsive to amphotericin B. The case was managed by a multidisciplinary approach involving the departments of ophthalmology, microbiology and pediatric infectious diseases. We want to draw attention once again that fungal keratitis caused by unusual agents are increasing. Physicians should consider fungal causes of keratitis, in patients with some predisposing factors like ocular surgery and prolonged use of topical corticosteroids.
Keywords: Fungal infection; paecilomyces; voriconazole; VORICONAZOLE; LILACINUS; HUMANS